EFFECTIVENESS OF USING CALL FOR TEACHING WRITING - Anna Nurawalia (Premise: Journal of English Education and Applied Linguistics, 2021)
Development of the networking system today give some possibilities for students’ learning language through CALL. Although there is a great benefit of computer assisted language learning on learners’ language performance in fact, yet many schools and universities do not utilize their classrooms and their computer laboratory to teach. The study used quantitative-qualitative data to investigate the effectiveness of CALL.Approach implemented in this research was experimental one group pre- post-test design. The total population of this study was 157 of the Health Department students in University of Aisyiah Yogyakarta of academic year 2019/2020 who took English For Daily Usage. Data was collected by student’s pre and post test and the interviewing process. Data was analyzed by using SPSS version 21. The students’ achievement data were taken from pre- and post-test tests’ result. This study serves other evidences toward how effective of using e-learning in our local teaching and learning environment supported by student’s higher proficiency score of their writing post-test. Approach applied and showed in https://unisayogya.learnsocial.online/ may overcome some shortcomings of traditional method of writing to some extent by providing feedback on students’ mistakes or errors.